Ett litet språks spår i översättarvärlden. På jakt efter ett svensk-polskt översättningsspråk - Data-Bukowska, Ewa (De Gruyter Open‎, 2014)
This paper looks into the issue of Swedish-Polish translationese as a manifestation of the Swedish centre impact on languages in the world via translation. The term “translationese” is used to describe a specific language created in translated texts, among other things in Swedish-to-Polish translation. Such a language may be postulated to influence contemporary Polish in some domains due to abundant translations of Swedish literature in Poland in recent years. What features can be then ascribed to the Swedish-Polish translationese, not only from a lexical but from a grammatical point of view as well? The paper addresses this question thorough an analysis of a Swedish literary text and its 33 Polish non-professional translations, which are assumed to maximize the tension between Swedish and Polish in translation underlying the development of translationese. However, the intention is not to characterize such a language as a whole, but to test some hypotheses in its delimitation. The propounded hypothesis is that the occurrence of a postulated feature in the majority of the collected translations may be seen as an indicator of this feature’s existence in the Swedish-Polish translationese as such. The following features are identified: frequent use of short sentences, possessive pronouns in an NP, underspecified expressions and repetitions of lexical items, as well as desolation of fixed phrases. The presented research may be an impute to a broader corpus-based contrastive study.
Keywords: translationese; the third code; Swedish/Polish; non-professional translation; język tekstów tłumaczonych; szwedzki/polski; przekład nieprofesjonalny